Analytical simulation of reinforced concrete beam with openings using ansys software - Ang, Yeong Leang (2014)
Reinforced concrete beam with openings have commonly used in the construction of structure due to aesthetic pleasant. So, beam is one of the important components for a structure and needed to be analysed and designed properly so that it can satisfy the strength and serviceability limitation. Although there have many existing commercial engineering software such as STAAD PRO, LUSAS, MATLAB and ANSYS, but finite element analysis is also known as ANSYS is become popular and widely used for solving engineering problems. ANSYS is a finite element modelling for numerically solving wide variety of structural analysis problems such as static structural analysis for both linear and nonlinear. This study is about the modelling of reinforced concrete beam with opening using ANSYS and CivilFEM 12.0 to determine the maximum deflection, displacement, stresses and strains under a set of loads. There are six random inputs will be used in this study such as Young Modulus (EX), Poison Ratio, Density, Area, and Fy Loads. The random output will be the graph of maximum deflection, displacement, stresses and strains. This study is going to be basic guidelines on how to implement the civil engineering element using ANSYS software.